Goodnight from London : a novel - Robson, Jennifer, 1970- (William Morrow, an imprint of HarperCollinsPublishers, 2017)
In the summer of 1940, ambitious young American journalist Ruby Sutton gets her big break: the chance to report on the European war as a staff writer for Picture Weekly newsmagazine in London. She jumps at the chance, for it's an opportunity not only to prove herself, but also to start fresh in a city and country that know nothing of her humble origins. But life in besieged Britain tests Ruby in ways she never imagined. Although most of Ruby's new colleagues welcome her, a few resent her presence, not only as an American but also as a woman. She is just beginning to find her feet, to feel at home in a country that is so familiar yet so foreign, when the bombs begin to fall. As the nightly horror of the Blitz stretches unbroken into weeks and months, Ruby must set aside her determination to remain an objective observer. When she loses everything but her life, and must depend upon the kindness of strangers, she learns for the first time the depth and measure of true friendshipand what it is to love a man who is burdened by secrets that arent his to share.